2016
DOI: 10.1038/srep26427
|View full text |Cite
|
Sign up to set email alerts
|

Increased arachidonic acid-containing phosphatidylcholine is associated with reactive microglia and astrocytes in the spinal cord after peripheral nerve injury

Abstract: Peripheral nerve injury (PNI) triggers cellular and molecular changes in the spinal cord. However, little is known about how the polyunsaturated fatty acid-containing phosphatidylcholines (PUFA-PCs) are regulated in the spinal cord after PNI and the association of PUFA-PCs with the non-neuronal cells within in the central nervous system (CNS). In this study, we found that arachidonic acid-containing phosphatidylcholine (AA-PC), [PC(16:0/20:4)+K]+, was significantly increased in the ipsilateral ventral and dors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…a suggested formation of GM1-bound Aβ (G-Aβ) species acting both as neuroprotective mechanism and promoting seed of Aβ aggregation [64][65][66]. Further, in line with these observations, the complementary pattern of the GM1 with the GM2/GM3 species, as well as presence of the PI, and LPI, further suggest the likely macrophage mediated lysosomal degradation of gangliosides at the plaque periphery, but not in the center of the Aβ plaques [46,67].…”
Section: Altered Gm Metabolism Is Associated With Aβ Plaque Core Formmentioning
confidence: 53%
See 1 more Smart Citation
“…a suggested formation of GM1-bound Aβ (G-Aβ) species acting both as neuroprotective mechanism and promoting seed of Aβ aggregation [64][65][66]. Further, in line with these observations, the complementary pattern of the GM1 with the GM2/GM3 species, as well as presence of the PI, and LPI, further suggest the likely macrophage mediated lysosomal degradation of gangliosides at the plaque periphery, but not in the center of the Aβ plaques [46,67].…”
Section: Altered Gm Metabolism Is Associated With Aβ Plaque Core Formmentioning
confidence: 53%
“…In addition, to the sphingolipid species, several phosphoinositol species, including LPI and PI were detected in the peripheral, diffuse structures of cored plaques. As demonstrated by MALDI-IMS, AA containing phospholipids are essential precursors in eicosanoid synthesis underlying microglial and astroglial mediated inflammatory response mechanisms [46]. Likewise LPI, the corresponding degradation product of LPI, a process mediated by cytosolic phospholipase A2 (PLA2) activity, has been shown to regulate neuroinflammation and neurodegeneration in AD [47,48].…”
Section: Maldi-ims Highlights Aβ Plaque Associated Sphingolipid and Pmentioning
confidence: 99%
“…Many studies have reported a close relationship between microglial function and n-3 PUFAs since then. N-3 PUFA supplementation reduces microglial activation and/or phenotype alteration in models of brain development (Kuperstein et al, 2008;Madore et al, 2014;Abiega et al, 2016), respiratory system development (Tenorio-Lopes et al, 2017), healthy aging (Grundy et al, 2014), ischemia (Zhang et al, 2010;Belayev et al, 2011;Okabe et al, 2011;Eady et al, 2012aEady et al, ,b, 2014Chang et al, 2013;Zendedel et al, 2015;Jiang et al, 2016), spinal cord injury (Huang et al, 2007;Lim et al, 2013a,b;Paterniti et al, 2014;Tremoleda et al, 2016;Xu et al, 2016), Parkinson's disease (Muntane et al, 2010;Ji et al, 2012;Tian et al, 2015;Delattre et al, 2017;Mori et al, 2017), AD (Lynch et al, 2007;Hopperton et al, 2016;Serini and Calviello, 2016;Wen et al, 2016), systemic inflammation (Delpech et al, 2015b), traumatic brain injury (Pu et al, 2013;Harrison et al, 2015;Harvey et al, 2015;Desai et al, 2016), neuropathic pain model (Xu et al, 2013b;Manzhulo et al, 2015;Huang and Tsai, 2016), aging (Labrousse et al, 2012), demyelination (Chen et al, 2014), amyotrophic lateral sclerosis…”
Section: Microglia As a Target For N-3 Pufas And Spmsmentioning
confidence: 99%
“…As such, we could suppose that there is a plausible link between increases in glial cell numbers and neuronal death profiles and the observations of metabolites. Supporting a facet of this, a recent study reports that the PC aa metabolites are enriched in the microglia, specifically in the spinal cord microglia after peripheral nerve injury [47] . In addition, the death of oligodendrocytes and the formation of a white-matter cyst is a key component of this model [35] .…”
Section: Time-series Analysismentioning
confidence: 72%